2017
DOI: 10.1017/s0007114517000678
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota of mice putatively modifies amino acid metabolism in the host brain

Abstract: Recently, it has been found that the gut microbiota influences functions of the host brain by affecting monoamine metabolism. The present study focused on the relationship between the gut microbiota and the brain amino acids. Specific pathogen-free (SPF) and germ-free (GF) mice were used as experimental models. Plasma and brain regions were sampled from mice at 7 and 16 weeks of age, and analysed for free d- and l-amino acids, which are believed to affect many physiological functions. At 7 weeks of age, plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 52 publications
1
70
0
Order By: Relevance
“…The Kawase team noted that l-arginine(l-Arg), l-glutamine(l-Gln), l-isoleucine(l-Ile), and l-leucine(l-Leu) were significantly higher in specific pathogen-free (SPF) mice than in germ-free (GF) mice. However, d-Aspartate, d-serine, and l-serine were higher in some brain regions of GF mice than in those of SPF mice [20].…”
Section: Potential Role Of D-glutamate In Brain-gut-microbiota Axismentioning
confidence: 69%
See 1 more Smart Citation
“…The Kawase team noted that l-arginine(l-Arg), l-glutamine(l-Gln), l-isoleucine(l-Ile), and l-leucine(l-Leu) were significantly higher in specific pathogen-free (SPF) mice than in germ-free (GF) mice. However, d-Aspartate, d-serine, and l-serine were higher in some brain regions of GF mice than in those of SPF mice [20].…”
Section: Potential Role Of D-glutamate In Brain-gut-microbiota Axismentioning
confidence: 69%
“…However, studies on d-glutamate are limited and their role in neurocognitive function remains unclear. Animal studies have reported higher d-glutamate levels in specific brain regions [19,20], and a pilot human study showed that d-glutamate levels are associated with cognitive functions in AD or MCI patients [21].…”
Section: Introductionmentioning
confidence: 99%
“…D-Asp was present in the nervous system of cephalopods and D-Ala in the muscle and hepatopancreas of crustaceans (Bender, 2012). Furthermore, the presence of D-Ser, D-Asp, and D-Ala was confirmed in plasma and brain tissues of both germ-free and specific pathogen-free mice (Kawase et al, 2017). These facts suggest that DAAO and D-Asp oxidase are necessary for the D-amino acids produced by intestinal bacteria and those provided by the animals.…”
Section: Introductionmentioning
confidence: 85%
“…Further research is needed to identify the central effects of glutamine in AN. Interestingly, Kawase et al focused recently on the relationship between the gut microbiota and the brain amino acids in specific pathogen-free (SPF) and germ-free (GF) mice [70]. L-glutamine concentrations were higher in SPF than in GF mice both in plasma and brain.…”
Section: Perspectives: Toward New Combined Strategies?mentioning
confidence: 99%